2003
DOI: 10.1002/mds.10541
|View full text |Cite
|
Sign up to set email alerts
|

Adult onset Niemann‐Pick type C disease: A clinical, neuroimaging and molecular genetic study

Abstract: We report on a patient with adult-onset Niemann-Pick type C (NPC) disease, carrying the mutations P1007 and I1061T in the NPC1 gene, presenting with marked psychiatric changes followed by dystonia and cognitive impairment. Filipin staining, single photon emission computed tomography perfusional, positron emission tomography metabolic, conventional magnetic resonance imaging, and magnetic resonance spectroscopy findings suggested a pathophysiological correlation with phenotype expression. This case expands the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 18 publications
3
17
0
3
Order By: Relevance
“…[21,22] Psychiatric changes are often followed by dystonia and cognitive impairment. [23] These findings are consistent with MRI and EEG findings in the present study. Clinical signs for NP-C include common features like cataplexy, seizures and dystonia.…”
Section: An Illustrative Casesupporting
confidence: 95%
“…[21,22] Psychiatric changes are often followed by dystonia and cognitive impairment. [23] These findings are consistent with MRI and EEG findings in the present study. Clinical signs for NP-C include common features like cataplexy, seizures and dystonia.…”
Section: An Illustrative Casesupporting
confidence: 95%
“…Tedeschi et al 15 described proton MR spectroscopy parameters in 10 (mostly adult) patients compared with controls and showed reduced NAA/creatine ratios in the caudate. Battisti et al 16 described significant frontal cortex, thalamic, and cerebellar hypoperfusion on FDG-PET associated with illness progression. Zaaraoui et al 17 compared 2 patients individually against a group of controls by using magnetization transfer ratio and found reductions in the thalamus, putamen and globus pallidus, and cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…This region of the spectrum is usually attributed to lipids, but in maple syrup disease is believed to represent resonances of methyl protons from branched chain amino acids and branched-chain α-keto acids that accumulate as a result of defective oxydative decarboxylation of leucine, isoleucine and valine [23]. Also 1 H-MRS studies on patients with Niemann-Pick type C disease have shown increased resonance intensity of the lipid region of the spectrum, probably due, in this case, to a defective metabolism of cholesterol with ceramide accumulation [24,25]. In both maple syrup and Niemann-Pick type C diseases, the abnormal broad peak detectable at 0.9 ppm seems to decrease with appropriate therapy [23,24].…”
Section: Diagnostic Specific 1 H-mrs Changesmentioning
confidence: 99%